(untitled) (Research Announcements "Heritage BG", 2025)
Five paintings with signatures of Anton Mitov, Boris Mitov, Yaroslav Veshin from the Dachev Collection were studied at the Centre for Archaeometry with Laboratory for Conservation and Restoration (CALCR) with X-ray fluorescence spectrometer (XRF), supplemented by Raman spectroscopy. The paintings were pre-examined under a microscope, UV, IR source, spectrophotometer and a colour analyser at the laboratory in the Institute of Ethnology and Folklore Studies with Ethnographic Museum (IEFSEM BAS) according a contract between the institute and the owner for an authentication of the collection. References: Dinova-Ruseva, V. (2004). Kragozorat na Yaroslav Veshin. – In: EK. Kulturen dvumesechnik. Darzhavna agentsia za balgarite v chuzhbina, No 4, 2–8. Ivanova, V. (2003). Myusyulmanski obrazi i stseni v tvorchestvoto na A. Mitov (1862–1930). – In: Balgarski folklor: spisanie za folkloristichni, etnolozhki i antropolozhki izsledvania, XXIX, No 2–3, 171–182. Karlukovska, S. (1992). Boris Mitov i akademizmat v balgarskoto izkustvo. – In: Problemi na izkustvoto, 1992, No 3–4, 47–53. Blockx, J. (1881). Peinture a l’huile: matériaux, définition des couleurs fixes et conseils pratiques, suivis d’une notice sur l’ambre dissous; compendium l’usage des artistes peintres. Gand.